Integration of accelerated MRI and post-processing software: a promising method for studies of knee osteoarthritis. Issue 11 (November 2016) - Duryea, J.; Cheng, C.; Schaefer, L.F.; Smith, S.; Madore, B.
Summary: Objective: Magnetic resonance imaging (MRI) is a widely used imaging modality for studies of knee osteoarthritis (OA). Compared to radiography, MRI offers exceptional soft tissue imaging and true three-dimensional (3D) visualization. However, MRI is expensive both due to the cost of acquisition and evaluation of the images. The goal of our study is to develop a new method to address the cost of MRI by combining innovative acquisition methods and automated post-processing software. Methods: Ten healthy volunteers were scanned with three different MRI protocols: A standard 3D dual-echo steady state (DESS) pulse sequence, an accelerated DESS (DESSAcc ), acquired at approximately half the time compared to DESS, and a multi-echo time DESS (DESSMTE ), which is capable of producing measurements of T2 relaxation time. A software tool was used to measure cartilage volume. Accuracy was quantified by comparing DESS to DESSAcc and DESSMTE and precision was measured using repeat readings and acquisitions. T2 precision was determined using duplicate DESSMTE acquisitions. Intra-class correlation coefficients (ICCs), root-mean square standard deviation (RMSSD), and the coefficient of variation (CoV) were used to quantify accuracy and precision. Results: The accuracies of DESSAcc and DESSMTE were CoV = 3.7% and CoV = 6.6% respectively, while precision was 3.8%, 3.0%, and 3.1% for DESS, DESSAcc and DESSMTE . T2 repositioning precision was 5.8%. Conclusion: The results demonstrate that accurate and precise quantification of cartilage volume is possible using a combination of substantially faster MRI acquisition and post-processing software. Precise measurements of cartilage T2 and volume can be made using the same acquisition.